Effectiveness of physical barriers in mitigating human–elephant negative interactions in North-East India - Das, Gitima; Selvan, Kanagaraj; Lahkar, Bibhuti; Gopi, Govindan Veeraswami (Frontiers in Conservation Science, 2022)
Physical barriers, like solar fences, elephant-proof trenches, stone, or rubble walls, are installed as conflict mitigation interventions in India's major Asian elephant (Elephas maximus) ranges. However, installations lacking a priori scientific assessment of site-specificity for reducing elephant incursion in the human settlements often fail in the intended goals of the resource-intensive management interventions. Since humans are central to conflict issues, research focusing on social aspects is essential for devising solutions. Despite the use of barriers in the Golaghat district in Assam, human-elephant conflict (HEC) cases are increasing, which offers an opportunity to evaluate their efficacy. Optimized hotspot analysis of the historic HEC records from 2010-2019 was done to check the spatial extent of the conflict and its dispersion in the district. We also assessed the efficiency of a 4.2 km long solar fence and a 2 km long elephant-proof trench through generalized linear modeling. We evaluated the encounter rates of elephant signs and other site covariates at the barrier and non-barrier sites. Multinomial logistic regression was applied to assess the perception of local people on the barriers and overall HEC in their areas based on their willingness to pay (WTP) for maintenance of the barriers. The highest cases occurred between 2016-2017, making up 25% of the total conflict cases. It was noticed that the extent of these hotspots was concentrated, and there was no dispersion of the conflict to other areas. Further, a significant difference in the encounter rates of elephant signs between barriers and no-barrier sites were observed. Solar fenced areas showed relatively lower encounter rates than areas with the trench, suggesting better efficiency of solar fencing than trench in the landscape. Besides, only five out of seven explanatory variables, viz., the persistence of HEC cases, amount of ex-gratia compensation, time taken in getting compensation, change in elephant behavior (incursion), and crop-raiding frequency significantly explained people’s perception of the barrier and non-barrier sites. According to local people, physical barriers are essential in managing HEC; hence, installing and maintaining solar fences in the high conflict hotspots is crucial for this landscape.